The Influence of Green Product and Green Promotion on Intention to Buy PT Unilever Indonesia Tbk Products Among Students at Universitas Mataram - BQ. Eka Sulistia Rahayu; Hilmiati, Hilmiati; Rusminah, Rusminah (Tinta Emas Publisher, 2023)
Today there is a tendency for companies to be required to produce in an environmentally friendly manner in addition to making a profit. Building a culture of environmentally friendly behavior requires patience and continuity, so that it can be felt in the future by all living things. This study aims to determine the effect of service quality on customer satisfaction in making purchases at the Tokopedia market place. This type of research uses associative research with a quantitative approach. The data collection method used is a sample survey method with data collected directly from respondents using a questionnaire. The population in this study were 100 consumers who had shopped at Tokopedia. The analysis tool used is Simple Linear Regression using SPSS version 25. The results showed that the R2 value was found to be 0.721 (72.1%) which indicates that the effect of the independent variable (quality of service) is .721% while 27.9% influenced by other variables. The results of the t test found that t count > t table on the service quality variable, namely 15.925 > 1.661. Thus the results of the study indicate that the influence of service quality has a positive and significant effect on consumer satisfaction at the Tokopedia market place.